If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5xa + -12xa = -35 Combine like terms: 5ax + -12ax = -7ax -7ax = -35 Solving -7ax = -35 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Divide each side by '-7x'. a = 5x-1 Simplifying a = 5x-1
| X+8=28+X | | 4y+8=3y | | 6q+2r-q+7r= | | -9d-4d=15 | | 129+191=n | | 10h-5h-4=6 | | 5a-12a=-35 | | 3x(3x-2)-4x(3x+4)= | | 13x+26=6x+180 | | 8q-5q= | | 9c-8=1 | | 2x-x=24-2x | | 20d-18d=2 | | 9y-6=-456 | | 7g=4 | | 17d-15d=20 | | 4n-6=94 | | x/4=3/4 | | 5x(2x+3)-2x(2x-1)= | | 2x-1/5=1 | | h=-16t^2+60t+2 | | 3a+6b+2a-5b= | | 2/7(x-4)=2 | | 2.20=12.15 | | 7x+2y-5x-5y= | | (5-2x)*(4-x)-2x*(x+6)=1-x | | 7(3x-5y)-4(4x-5y)= | | 6y+11=4 | | -5/7x7/4 | | 10(x-1)=10 | | -7x-10+4x=20 | | 3(y+1)=0 |